Essays on corporate debt structure - Pham, Ngoc Anh (2020)
This thesis discusses two aspects of debt structure and is divided into three essays. The first essay examines the decision of whether to use fixed- or floating-rate debt. The liquid and deep swap markets in most countries enable firms to issue any type of debt that is cheaper and then swap it into their preferred structure. If firms are hedging, then their choices of interest rate exposures should be driven by the sensitivity of their cash flows to interest rates. Alternatively, if firms are timing the market to reduce their cost of capital, then the selection of those exposures should be driven by the interest rate movements. The second essay attempts to determine what factors they consider to be important when firms use foreign currency debt. The currency debt mix is important for many firms and in particular multinationals, which generate some of their revenues in foreign currency and are therefore exposed to movements of currencies in which these revenues are denominated. Funding in currencies where the firm operates to hedge exposure is an alternative to the use of foreign currency derivatives. The third essay examines the relationship between the corporate use of interest rate swaps and the probability of default. This study attempts to answer the question of whether firms are hedging or speculating when using interest rate swaps. This thesis uses a large hand collected dataset of UK non-financial firms during the period from 1999 to 2015, which covers two distinct periods of contrasting economic fortune. The global 2007 financial crisis is an event that could affect the selection of interest rate and foreign exchange exposure of corporate debt. Previous studies have to manually make the adjustment to a firm’s pre-derivative debt structure to arrive at the net of derivative debt profile. In the UK, data is reported after the effect of derivatives. The data, therefore, is potentially more accurate than that employed by previous US studies. Additional data on the direction of interest rate and foreign currency swaps were also collected, which provides additional insight into debt structure and firm risk management.